Breast Cancer: Does Type of Hospital Where You Get Surgery Affect Survival?. Issue 1 (January 2019) - Lin, Jenny J.; Egorova, Natalia; Franco, Rebeca; Bickell, Nina A.
Abstract : ABSTRACT: Under the Affordable Care Act (ACA), more women are insured with Medicaid, which should improve healthcare access. We sought to determine whether there are survival differences among patients with breast cancer undergoing surgery at facilities with varying proportions of Medicaid patients. We used New York State (NYS) Vital Statistics death records data linked with NYS discharge inpatient and ambulatory surgery databases to examine 90-day survival after surgery from 2008 to 2013. We used all Medicaid discharges to calculate and create quintiles of facilities based on Medicaid volume. We calculated survival hazard ratios using a marginal Cox model controlling for clustering of patients within hospitals, age, race, insurance, year of surgery, and comorbidities. Women who received surgery in facilities with the highest quintile of Medicaid volume had higher 90-day mortality (2.1% vs. 0.07%, p < .001) compared with those treated in facilities with lowest Medicaid volume, even after adjusting for multiple confounders. Consequently, although the ACA may improve access, healthcare quality remains questionable because patients treated at facilities with high proportions of Medicaid volume appear to have worse 90-day survival, likely due to quality of surgical and postsurgical care. Policymakers must ensure that quality of care is not negatively impacted by programs to reduce costs.